The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1177/026565909300900202
|View full text |Cite
|
Sign up to set email alerts
|

A treatment programme for improving story-telling ability: a case study

Abstract: The purpose of the present investigation was to measure the effects of a treatment programme on the story-telling ability of a second-grade language/learning-disabled male. Treatment was conducted twice a week for a period of 12 weeks. Results revealed an improvement in both the length and complexity of the subject's oral stories. These results are discussed relative to the role of language treatment on academic success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 6 publications
(4 reference statements)
1
15
0
Order By: Relevance
“…The designs of each study were classified as follows: Two studies (Adams, 2001;Klecan-Aker, 1993) were identified as "case studies"; that is, a study with uncontrolled observation (descriptive) report of events and outcomes in one or more participants. Two studies (Adams, Lloyd, Aldred, & Baxendale, 2006;Swanson et al, 2005) used "case series" designs whereby pretest-posttest data were collected across a sequence of individual participants.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The designs of each study were classified as follows: Two studies (Adams, 2001;Klecan-Aker, 1993) were identified as "case studies"; that is, a study with uncontrolled observation (descriptive) report of events and outcomes in one or more participants. Two studies (Adams, Lloyd, Aldred, & Baxendale, 2006;Swanson et al, 2005) used "case series" designs whereby pretest-posttest data were collected across a sequence of individual participants.…”
Section: Methodsmentioning
confidence: 99%
“…The quality indicator scores for the studies ranged from 0 to 4 out of a possible 6 points for study protocol description, blinding, sampling/allocation, treatment fidelity, significance, and practical significance. Five of the eight studies provided sufficient description of the study protocol so that the treatment could be replicated (Adams et al, 2006;Dollaghan & Kaston, 1986;Klecan-Aker, 1993;Richardson & Klecan-Aker, 2000;Swanson et al, 2005); however, only two studies (Adams, 2001;Swanson et al, 2005) explicitly stated that the assessors were blind to the study conditions. None of the studies used random assignment.…”
Section: Methodsology Quality and Research Stagementioning
confidence: 99%
See 3 more Smart Citations